Pengembangan Sistem Informasi Pasar Lokal Untuk Mendukung Usaha Mikro Kecil Dan Menengah Di Kabupaten Sumba Barat Daya - Ongki Sairo Malo; Stefanus D.I.Mau; Diana Reby Sabawaly (GLOBAL SCIENTS PUBLISHER, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the regional economy, including in Southwest Sumba Regency. However, most MSMEs still face limitations in marketing, transaction management, and manual business data recording. This research aims to develop a web-based local market information system to support MSME digital sales and marketing activities. The research method used was Research and Development (R&D), with stages including needs analysis, system design, development, and system testing. The system was developed using a Model–View–Controller (MVC) architecture to separate application logic, display, and data management. The results show that the developed information system can improve business management efficiency, expand product marketing reach, and provide real-time transaction data and sales reports. With features such as a product catalog, shopping cart, checkout, and payment confirmation, this system is expected to increase MSME competitiveness and support the development of a digital-based local market in Southwest Sumba Regency.